Sacred and secret stories in professional knowledge landscapes: learner agency in teacher professional learning. Issue 5 (3rd September 2017) - Charteris, Jennifer; Smith, Jane
Abstract: Set in a schooling practitioner research context, this article critiques instrumental forms of teacher professional development. An account of teacher professional learning and development is provided, as an inter-relational construct, where teachers reflect on practice to inquire into their students' learning and foster their own and others specific interests and talents in creative ways. In an Aotearoa/New Zealand context, teachers are mandated to inquire into what their students need to know and understand, the strategies required for teachers to attain these learning goals, and how effective the approach implemented is in enhancing student learning. Emerging from qualitative case study research, a teacher's narrative account of a student-initiated critical thinking episode in a secondary science classroom is analysed to demonstrate sacred, secret and cover stories of professional knowledge landscapes. Findings highlight the importance of agentic teacher-enacted forms of practitioner inquiry that support critical and collaborative reflective practice.